(untitled) - 1978-; Arnett, Will; 1980-; Bell, Kristen; 1972-; Duhamel, Josh; Marcus, Andrew; Folsey, Ryan; 1970-; Bailey, John; 1951-; Young, Christopher; et al. (Distributed by Buena Vista Home Entertainment., 2010)
An ambitious young New Yorker, disillusioned with romance, takes a whirlwind trip to Rome, where she defiantly plucks magic coins from a fountain of love, inexplicably igniting the passion of an odd group of suitors: a sausage magnate, a street magician, an adoring painter, and a self-admiring model. But when a charming reporter pursues her with equal zest, how will she know if his love is the real thing?
Keywords: Drama; Man-woman relationships; Drama; Museum curators; Rome (Italy); Drama; New York (N.Y.); Drama; Feature films; Video recordings for the hearing impaired; Fiction films; Romantic comedy films